Diphtheria Outbreak During Covid-19 Pandemic in Katsina, North-Western Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context:The impact of coronavirus disease 2019 (COVID-19) pandemic on vaccine-preventable diseases, including diphtheria, may hamper the previous gains made in the eradication of the disease.Aims:We report the epidemiological profile, clinical features, laboratory findings, and hospitalization outcomes amongst cases of diphtheria managed at Federal Medical Centre, Katsina, Nigeria during the first wave of COVID-19 pandemic.Settings and Design:This was a retrospective review of cases of diphtheria managed between July and December 2020.Methods and Material:We extracted the clinical (socio-demographics, clinical features, and hospitalization outcomes) and laboratory findings (full blood counts, electrolytes, urea and creatinine) from the record of the children.Statistical Analysis Used:Using SPSS, we carried out a descriptive analysis and applied binary logistic regression to determine factors associated with death. Level of statistical significance was set atP< 0.05.Results:A total of 35 cases of diphtheria were admitted and managed from 1 July to 31 December 2020. The mean age of the children was 7.6 ± 3.1 years. Males were 15 (42.9%). There were 24 deaths (case fatality of 68.6%). Clinical findings were comparable between survivors and non-survivors except the bull neck, which was more common among non-survivors (P= 0.022). The median duration of hospitalization was shorter in those that died (P= 0.001). The age, sex, immunization status, leukocytosis, and biochemical features of renal impairments were not predictive of deaths. Prescence of bull neck was predictive of death (adjusted odds ratio 2.115, 95% CI 1.270, 3.521).Conclusions:The study shows a high number of cases of diphtheria over a short period of six months with high mortality. Amongst the clinical and laboratory variables, only presence of bull neck was predictive of death.